2022
DOI: 10.1109/access.2022.3183105
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria Evaluation of Portable Energy Storage Technologies for Electric Vehicles

Abstract: The conventional vehicles are a major cause of the greenhouse gases emissions in the global environment. Electric vehicles are a sustainable alternative to the conventional vehicles due to the negligible emissions and the possibility of the renewable energy integration. However, the electric vehicles require the separate storage systems and the selection of the proper storage system is a major concern in the electric vehicles markets. The storage system should be selected in a systematic and rational way. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The AHP method (with five criteria) was also applied in a similar study. Results showed that cost is the biggest problem in the implementation of LIBs [18]. A new framework for the evaluation of energy storage was also developed based on MCMD methods.…”
Section: Electric Vehicle Charging Stationsmentioning
confidence: 99%
“…The AHP method (with five criteria) was also applied in a similar study. Results showed that cost is the biggest problem in the implementation of LIBs [18]. A new framework for the evaluation of energy storage was also developed based on MCMD methods.…”
Section: Electric Vehicle Charging Stationsmentioning
confidence: 99%
“…Güner combined the AHP and TOPSIS methods to measure the service quality and rank the bus transit routes, showing the opportunity to monitor and improve the quality of bus transit service [101]. Liaqat et al directed their research toward evaluating portable energy storage technologies for electric vehicles with the AHP method [102]. Lee focused on prioritizing advanced public transport modes considering urban types in Korea, for which the AHP method was used [103].…”
Section: Mcda Applications In Transportmentioning
confidence: 99%
“…The human society is extremely dependent on transportation. According to statistics, there are about more than 1.4 billion vehicles in the world [3]. Tens of millions or even hundreds of millions of drivers manipulate vehicles around the world every day, which is a very large consumption of manpower [4].…”
Section: Introductionmentioning
confidence: 99%